A efficacy of different buffer size on latency of network on chip (NoC) - Farah Wahida Binti Zulkefli; P. Ehkan; M. N. M. Warip; Ng. Yen. Phing (Institute of Advanced Engineering and Science, 2019)
Moore's prediction has been used to set targets for research and development in semiconductor industry for years now. A burgeoning number of processing cores on a chip demand competent and scalable communication architecture such as network-on-chip (NoC). NoC technology applies networking theory and methods to on-chip communication and brings noteworthy improvements over conventional bus and crossbar interconnections. Calculated performances such as latency, throughput, and bandwidth are characterized at design time to assured the performance of NoC. However, if communication pattern or parameters set like buffer size need to be altered, there might result in large area and power consumption or increased latency. Routers with large input buffers improve the efficiency of NoC communication while routers with small buffers reduce power consumption but result in high latency. This paper intention is to validate that size of buffer exert influence to NoC performance in several different network topologies. It is concluded that the way in which routers are interrelated or arranged affect NoC’s performance (latency) where different buffer sizes were adapted. That is why buffering requirements for different routers may vary based on their location in the network and the tasks assigned to them.